Curcumin for parkinson´s disease: potential therapeutic effects, molecular mechanisms, and nanoformulations to enhance its efficacy - Cortés, Hernán; Reyes-Hernández, Octavio D.; Gonzalez-Torres, Maykel; Vizcaino-Dorado, Pablo A.; Del Prado-Audelo, Maria Luisa; Alcalá-Alcalá, Sergio; Sharifi-Rad, Javad; Figueroa-González, Gabriela; González-Del Carmen, Manuel; Florán, Benjamín; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2021)
Parkinson's disease (PD) is one of the most prevalent neurodegenerative disorders worldwide. It is caused by the degeneration of dopaminergic neurons from the substantia nigra pars compacta. This neuronal loss causes the dopamine deficiency that leads to a series of functional changes within the basal ganglia, producing motor control abnormalities. L-DOPA is considered the gold standard for PD treatment, and it may alleviate its clinical manifestations for some time. However, its prolonged administration produces tolerance and several severe side effects, including dyskinesias and gastrointestinal disorders. Thus, there is an urgent need to find effective medications, and current trends have proposed some natural products as emerging options for this purpose. Concerning this, curcumin represents a promising bioactive compound with high therapeutic potential. Diverse studies in cellular and animal models have suggested that curcumin could be employed for the treatment of PD. Therefore, the objective of this narrative mini-review is to present an overview of the possible therapeutic effects of curcumin and the subjacent molecular mechanisms. Moreover, we describe several possible nanocarrier-based approaches to improve the bioavailability of curcumin and enhance its biological activity.